The Relationship Between Stress And Online Learning Achievement During Covid-19 In Class XI Students At SMA Negeri 1 Deli Tua District Deli Tua District Deli Serdang District Year 2021 - Mona Fitri Gurusinga; Afrilius Simanjuntak (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Stress is a psychological response to various stressors that can occur in every individual, including high school students. Stress can be one of the factors that can affect a person's learning achievement. During the Covid-19 pandemic, students were directed to take part in the online learning process, which caused most students to get various kinds of stressors that caused stress to have an impact on learning achievement. Learning achievement is an indicator of student learning outcomes obtained from teaching and learning activities carried out. This study aims to determine the relationship between stress and student achievement in class XI at SMA N 1 Deli Tua. This study uses a cross-sectional research design which was conducted in January 2021 at SMA N 1 Deli Tua. The sample of this study amounted to 71 students who have different stress level criteria. Stress level data was collected using the standard DASS-42 questionnaire, and learning achievement data used a documentation technique, namely the recap of the average value of semester 2 report. The data were analyzed using the chi-square test. The results of the study with the chi-square test obtained p value = 0.001 <0.05, so Ha is accepted, which means that there is a significant relationship between stress and student achievement in class XI at SMA N 1 Deli Tua. The conclusion of this study shows that there is a significant relationship between stress and online learning achievement results during Covid-19 in class XI MIA students at SMA Negeri 1 Deli Tua in 2021.